Response of Glucocorticoid Receptor Alpha and Histone Deacetylase 2 to Glucocorticoid Treatment Predicts the Prognosis of Sudden Sensorineural Hearing Loss - Xiuling Zhang; Jinxiang Chen; Ziwen Gao; Hui Qi; Yanhong Dai; Wandong She (Clinical and Experimental Otorhinolaryngology, 2019)
Objectives To investigate glucocorticoid receptor (GR) and histone deacetylase 2 (HDAC2) gene expression and protein levels in peripheral blood mononuclear cells (PBMCs) of patients with severe or profound sudden sensorineural hearing loss (SSNHL) and to explore the roles of GRs and HDAC2 in glucocorticoid (GC) insensitivity. Methods Fifty-five severe or profound SSNHL patients were enrolled in the study. According to hearing improvement after GC treatment, patients were assigned into two groups: GC-sensitive and GC-resistant. A normal reference group included 20 healthy volunteers without hearing loss. Quantitative real-time polymerase chain reaction and Western blot analyses were used to detect the relative expression of GRα, GRβ, and HDAC2 in PBMCs at the mRNA and protein levels. Results The protein levels of GRs and HDAC2 in PBMCs of SSNHL patients were lower than the normal reference values before GC treatment. Compared with the GC-resistant group, both the mRNA and protein levels of GRα and HDAC2 were significantly increased in the GC-sensitive group after GC treatment. Conclusion A lack of GRα and HDAC2 induction following steroid treatment in GC-resistant SSNHL patients may play a fundamental mechanistic role in GC insensitivity. Response of GRα and HDAC2 to steroid treatment may, thus, predict the prognosis of hearing improvement in SSNHL patients.